1981
DOI: 10.1017/s0021859600032081
|View full text |Cite
|
Sign up to set email alerts
|

A revised model for the estimation of protein degradability in the rumen

Abstract: Estimates of the degradability of protein in the rumen are essential for the application of new systems which have been suggested for the evaluation of the protein requirements of ruminants (Agricultural Research Council, 1980). The effective percentage degradability (P) of protein supplements in the rumen is dependent not only on the course of degradation of the protein particles in the rumen, but also on the time distribution of their stay in the rumen, and will decrease if there is an increase in the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
355
0
34

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(391 citation statements)
references
References 1 publication
2
355
0
34
Order By: Relevance
“…The nonlinear parameters a, b and c and effective degradability of DM (EDDM) were calculated using the Neway computer program (McDonald, 1981) …”
Section: In Situ Digestibility Analysesmentioning
confidence: 99%
“…The nonlinear parameters a, b and c and effective degradability of DM (EDDM) were calculated using the Neway computer program (McDonald, 1981) …”
Section: In Situ Digestibility Analysesmentioning
confidence: 99%
“…Regarding to the parameter estimate values, Feitosa (1999), studying the comparison of models in rehearsals of degradability in situ with coastcross grass hay, observed that the model of McDonald (1981), also corrected for the colonization time, resulted in the same estimates for the model of Mertens & Loften (1980). This author reports values of 43.26% for insoluble and non-degradable fraction; 4.4%h -1 for the degradation rate (parameter c) and 2.45 hours for the time of colonization.…”
Section: Resultsmentioning
confidence: 99%
“…A DIVVMO foi calculada segundo a técnica descrita por Silveira (2002), e a degradabilidade efetiva da proteína, mediante a incubação ruminal de amostras de feno, segundo Gonzáles et al (1990) revisado por Huntington & Givens (1995), e os resultados foram ajustados ao modelo proposto por McDonald (1981).…”
Section: Methodsunclassified